ІНФОРМАЦІЙНІ ПОСЛУГИ ЯК ЗАСІБ ЗАБЕЗПЕЧЕННЯ ІНФОРМАЦІЙНОЇ ДІЯЛЬНОСТІ ОРГАНІВ ДЕРЖАВНОЇ ФІСКАЛЬНОЇ СЛУЖБИ УКРАЇНИ - Литвин, Наталія Анатоліївна (SUPREMANCE OF LAW, 2019)
The article is devoted to the study of information services as a means of providing information activities of the bodies of the State Fiscal Service of Ukraine. It is stated that the provision of information services by the public authorities to the citizens on the basis of electronic information resources using the Internet is extremely important for improving the efficiency of the SFS bodies of Ukraine. It is noted that the provision of administrative information services is not only a guaranteed function of the state, which declares publicity, openness and publicity within the framework of tax information relations, but also an inalienable right of citizens of Ukraine to obtain the necessary information from tax and customs authorities. It is proved the necessity for improvement and further development of electronic interaction between the authorities of the SFS of Ukraine and subjects of information tax and customs legal relationship, which consists in full transition of the authorities of the SFS of Ukraine to contactless communication, firstof all with natural and incorporated persons- taxpayers. On the basis of it the following main stages of transition of fiscal authorities to providing information services on a contactless basis are offered: - the first stage provides the placement of information on possible places and regimes of service provision on the Internet, as well as the publication of forms and application forms, which are provided by the subjects of tax and customs legal relationship to the authorities of the SFS of Ukraine in order to realize the right to information services, with examples of their filling; - the second stage - the opportunity to fill the necessary electronicforms of documents in the applicant’s workplace for their further submission to the fiscal authorities; - the third stage provides a possibility of realization of departure of the filled electronic forms of the documents, necessary for receiving information service, to tax and customs authorities by means of telecommunication channels by subjects of tax and customs legal relationship, preliminary examination of these documents by the authorities of the SFS of Ukraine and also a possibility of visit and making an appointment; - the fourth stage is the possibility of providing information service to subjects of tax and customs legal relationship in an electronic format, without visiting of fiscal authority.
Keywords: information; administrative services; information services; legal entities; tax and customs authorities